Palladium-Catalyzed Synthesis of Fluorenes by Intramolecular C(sp2)–H Activation at Room Temperature - Tanji, Yutaka; Tsuji, Yasushi; Fujihara, Tetsuaki (Synlett, 2020)
The synthesis of fluorenes by intramolecular Pd-catalyzed C(sp2)–H activation of 2-arylbenzyl chlorides was conducted at room temperature by using commercially available triphenylphosphine and pivalic acid as ligands. The desired reactions proceeded efficiently at room temperature, and various substrates were converted into the corresponding fluorene derivatives in excellent yields.
Keywords: palladium catalysis; ligands; C–H activation; fluorenes; cyclization